IMPLIKASI FIKIH DAN KONVENSI HAK ANAK DALAM PENETAPAN USIA NIKAH: STUDI HUKUM POSITIF INDONESIA DAN NEGARA-NEGARA TIMUR TENGAH - Ulum, Moh. Rafiqil (Fakultas Syariah (Syari'ah Faculty ), 2025)
The age of marriage is an important global issue in the protection of children's rights, with states setting a minimum age of marriage to prevent the negative impacts of early marriage. In Muslim-majority countries, Islamic law or fiqh influences marriage policy, with age variations depending on the interpretation of the sect. While many countries have ratified the Convention on the Rights of the Child (CRC), challenges in balancing religious norms with international obligations remain. This research aims to understand the implications of fiqh and the CRC in setting the age of marriage in Indonesia and Middle Eastern countries and explain the harmonization or tension between the two, using normative methods and a qualitative analysis of literature. This research shows that fiqh with its various madhhabs provides guidance on the age of marriage that considers the physical, mental and emotional maturity of individuals, for example Hanafi sets 18 years for men and 17 years for women, Maliki sets 18 years for both sexes, while Syafii and Hanbali view 15 years as the minimum age. On the other hand, the Convention on the Rights of the Child (CRC) pushes the minimum age of marriage at 18 to protect children's rights from early marriage. In Indonesia, the revision of the Marriage Law from 1974 to Law No. 16 of 2019 sets the minimum age at 19 years, reflecting a commitment to children's rights and harmonization between Islamic law, national law and international standards. Middle Eastern countries such as Saudi Arabia, Egypt, Pakistan and Bahrain also set the minimum age at 18, demonstrating efforts to conform to the CRC and improve the welfare of children.